The Design for Emancipatory Quran Interpretation Learning to Deradicalize Students’ Quran Understanding - Karman, Karman; Anwar, Rosihon; Syarifudin, U.; Muhtar, S.N. (Jurnal Pendidikan Islam, 2021)
The understanding on Quran requires an approach that is oriented toward inclusiveness. Many Quran interpretation scholars who understand the Quran in a way that leads to antagonistic attitudes and acts of violence. There is a need to propose alternative Quran Interpretation Learning using an integrative approach. This paper aims to investigate the design of an integrated emancipatory Quran interpretation learning at Master Program for Arabic Language Education of UIN Sunan Gunung Djati Bandung. This research is qualitative using descriptive methods. It applied observation, interviews, and documentation to collect the data. Using scientific integrative approach, this study found that emancipatory Quran learning interpretation was designed into three levels: objectives, process and learning material.